Evaluation of a online-based self-help program for patients with panic disorder: randomized controlled trial - Lalk, Christopher; Väth, Teresa; Hanraths, Sofie; Prüßner, Luise; Timm, Christina; Hartmann, Steffen; Barnow, Sven; Rubel, Julian (Journal of medical internet research, 2025)
Background: Panic disorder is an anxiety disorder marked by severe fear of panic attacks in the absence of causes. Agoraphobia is a related anxiety disorder, which involves fear and avoidance of specific situations in which escape or help may be difficult. Both can be debilitating and impair well-being. One treatment option may be internet-based cognitive behavioral therapy (iCBT), which allows large-scale application and may overcome treatment barriers for some individuals. - Objective: This study aimed to evaluated the effectiveness of a novel online self-help intervention for panic disorder with or without agoraphobia. As our primary hypotheses, we expected the intervention to improve panic and agoraphobia symptoms and well-being. Our secondary hypotheses entailed improvements in daily functioning, mental health literacy, working ability, and health care use in the intervention group. - Methods: German-speaking patients (N=156) aged 18-65 years with internet access and a diagnosis of panic disorder with or without agoraphobia were recruited for this randomized controlled trial. The intervention group (n=82) received access to a 12-week online self-help program entailing psychoeducation, cognitive restructuring, exposure, and mindfulness elements. The control group (n=72) received care as usual during the study period and was offered the prospect of using the program after 12 weeks. The primary outcomes were assessed via the Panic and Agoraphobia Scale (PAS) and the WHO (World Health Organization)-5 Well-Being Index (WHO-5). Mixed effect models were computed using multivariate imputation by chained equation for the analysis of intervention effects. - Results: In the intervention group, participants completed on average 7.3 out of 12 (60.8%) modules, and 27 out of 82 (32.1%) participants finished the whole course. Changes in PAS revealed a significant effect in favor of the intervention group (t110.1=-2.22, Padj=.03) with a small to moderate effect size (d=-0.37, 95% CI -0.70 to -0.04). No significant effect was found for the second primary outcome WHO-5 (t149.8=1.35, Padj=.09) or the secondary outcomes. Improvements were observed in anxiety (t206.8=-4.12; P<.001; Cohen d=-0.60, 95% CI -0.089 to -0.32) and depression (t257.4=-3.20; P<.001; Cohen d=-0.41 95% CI -0.66 to -0.16). No negative effects were associated with the intervention (t125=-1.14, P=.26). - Conclusions: The presented online intervention can help reduce the core symptomatology of panic disorder and agoraphobia, as well as anxiety symptoms and associated depression. No effects were found for well-being and secondary outcomes. This may be due to higher illness burden in the intervention group and possibly the COVID pandemic, which caused unique challenges to patients suffering from panic disorder. Therefore, further research and intervention adaptations may be warranted to improve these outcomes. - Trial Registration: German Clinical Trials Register DRKS00023800; https://drks.de/search/en/trial/DRKS00023800